Acinetobacter baumannii Infection and IL-17 Mediated Immunity. (9th February 2016) - Yan, Zihe; Yang, Junjun; Hu, Renjing; Hu, Xichi; Chen, Kong
Abstract : Acinetobacter baumannii is a significant cause of severe hospital-acquired infections with a recent rise in multidrug-resistant infections involving traumatic wounds of military personnel. The interleukin-17 (IL-17) pathway is essential for neutrophil recruitment in response to a variety of pathogens, while the control of A. baumannii infection is known to be dependent on neutrophils. This suggests that IL-17 may play an important role in A. baumannii infection; however, this has yet to be studied. Here, we summarize the recent advances in understanding the host-pathogen interaction of A. baumannii and propose a potential role of the IL-17 pathway in generating a protective immune response.